Mechanisms and therapeutic strategies of macrophages and neutrophils inducing ulcerative colitis progression - Wang, Haogeng; Huang, Taixi; Ma, Yuxia (Frontiers in Immunology, 2025)
Ulcerative colitis (UC) is a kind of chronic inflammatory bowel disease, is driven by dysregulated immune responses involving neutrophils (NEUs) and macrophages. NEUs exacerbate mucosal injury through reactive oxygen species (ROS), neutrophil extracellular traps (NETs), proteases, and cytokine interactions, while also exhibiting dual roles in tissue repair. Macrophages contribute to UC progression via M1-mediated pro-inflammatory cytokine release and epithelial barrier disruption, whereas M2 macrophages promote resolution through anti-inflammatory signals (IL-10, TGF-β) and epithelial regeneration. Clinically, NEU-derived biomarkers predict disease activity and therapeutic response, while macrophage-targeted therapies modulate inflammation. This review summairzes current knowledge on the mechanistic roles of these immune cells in UC pathogenesis and their clinical implications, such as NET inhibition, MMP-9 blockade, and M2 polarization, which hold promise for precision medicine in UC.